2019
DOI: 10.1109/access.2019.2904095
|View full text |Cite
|
Sign up to set email alerts
|

Personal Identification Using a Robust Eigen ECG Network Based on Time-Frequency Representations of ECG Signals

Abstract: This paper is concerned with personal identification using a robust EigenECG network (REECGNet) based on time-frequency representations of electrocardiogram (ECG) signals. For this purpose, we use a robust principal component analysis network (RPCANet) and wavelet analysis. In general, PCA performance and applicability in real case scenarios is limited by the lack of robustness to outliers and corrupted observations. However, in a real nonstationary ECG noise environment, RPCA shows good performance when the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…As a result, the authors in [27] reported 100% identification accuracy using ECG data of 21 subjects. Lee et al [28] proposed an algorithm based on a time frequency representation of the ECG data. Both the robust principal components analysis network (RPCANet) and DWT methods were utilized for feature extraction.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the authors in [27] reported 100% identification accuracy using ECG data of 21 subjects. Lee et al [28] proposed an algorithm based on a time frequency representation of the ECG data. Both the robust principal components analysis network (RPCANet) and DWT methods were utilized for feature extraction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Both the robust principal components analysis network (RPCANet) and DWT methods were utilized for feature extraction. The support vector machine (SVM) was used for ECG classification [28]. Similarly, Arwa et al [29] introduced a wavelet-based method which utilizes the ECG power and energy features for personal identification.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides, the residual network is employed to present an ECG biometric authentication method, which can improve the generalization ability of the method on different ECG signals sampled in the different environments for the matching task [29]. In [89], the features are extracted by the principal component analysis network (PCANet) and then a robust Eigen ECG network (REECGNet) is used on time-frequency representations of ECGs for personal identification. Gated Recurrent Unit (GRU) based method in a bidirectional manner is proposed for human identification from ECG [111].…”
Section: Human Identificationmentioning
confidence: 99%
“…[129] proposed a modified U-net to handle varied length ECG for classification and R-peak detection. PCANet [22], an image classification model working with the help of cascaded principal component analysis (PCA), binary hashing, and blockwise histograms, is modified for biometric human identification task in non-stationary ECG noise environment [89]. But its effect remains to be evaluated with the state-of-thearts baselines introduced in the above sections.…”
Section: Fc and Othersmentioning
confidence: 99%
“…Li et al proposed a genetic algorithm-back propagation neural network (GA-BPNN) classification method based on wavelet packet decomposition feature extraction [18]. Lee and Kwak introduced a time-frequency representation (WT method) of ECG signal for personal identification [19]. Venkatesan et al developed a remote healthcare system where discrete wavelet transform (DWT) is implemented on the heart rate variability (HRV) feature extraction [20].…”
Section: Introductionmentioning
confidence: 99%